2016
DOI: 10.1089/hgtb.2015.106
|View full text |Cite
|
Sign up to set email alerts
|

Retroviral Replicating Vectors Deliver Cytosine Deaminase Leading to Targeted 5-Fluorouracil-Mediated Cytotoxicity in Multiple Human Cancer Types

Abstract: Toca 511 is a modified retroviral replicating vector based on Moloney c-retrovirus with an amphotropic envelope. As an investigational cancer treatment, Toca 511 preferentially infects cancer cells without direct cell lysis and encodes an enhanced yeast cytosine deaminase that converts the antifungal drug 5-fluorocytosine to the anticancer drug, 5-fluorouracil. A panel of established human cancer cell lines, derived from glioblastoma, colon, and breast cancer tissue, was used to evaluate parameters critical fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…As shown previously in a variety of other malignancies [27,28,36], here we show that RRV also shows efficient and selective infection of all human and murine PDAC cells tested in vitro. After inoculation of RRV-GFP, the percentage of GFP positive cells increased logarithmically and remained persistently high, at levels of 90% or more, through serial passages.…”
Section: Discussionsupporting
confidence: 89%
“…As shown previously in a variety of other malignancies [27,28,36], here we show that RRV also shows efficient and selective infection of all human and murine PDAC cells tested in vitro. After inoculation of RRV-GFP, the percentage of GFP positive cells increased logarithmically and remained persistently high, at levels of 90% or more, through serial passages.…”
Section: Discussionsupporting
confidence: 89%
“… 2–4 We have shown that this treatment modality has broad applicability in multiple tumor types. 5 , 6 Additionally, we and our colleagues (Hiraoka et al, accompanying article) show that this therapeutic approach also exerts an extended immunotherapeutic effect. These data are further supported by an abundance of evidence that cytotoxic anticancer drugs, including 5-FU, can promote antitumor immune responses.…”
mentioning
confidence: 82%
“…Breton and colleagues performed a study using a modified Ankara virus to express yeast CD in situ, reducing tumor growth in a glioblastoma mouse model (10). After introducing a viral vector for in vitro transformation of several cancer cell lines (12,31) and evaluation in preclinical models (32) not detected significant immunogenicity of bCD in animals (33,34). We do not anticipate that bCD 1525 would have immunogenic properties different from those of the regular protein, but this should be evaluated before translation to human use.…”
Section: Discussionmentioning
confidence: 99%
“…To minimize sideeffects of 5-FU, targeted delivery of bCD to tumor cells coupled with systemic administration of 5-FC is also being considered. Monoclonal antibodies conjugated to the enzyme, as well as viral vectors and non-viral vectors, have been used to achieve this goal (6)(7)(8)(9)(10)(11)(12)(13). Recent studies have demonstrated prostate cancer cell-specific nanoparticle delivery of bCD to tumor xenografts by specific targeting of prostate-specific membrane antigen that resulted in improved tumor control (13,14) following localized conversion of 5-FC to 5-FU.…”
mentioning
confidence: 99%